2021
DOI: 10.3389/fmolb.2021.701975
|View full text |Cite
|
Sign up to set email alerts
|

Moonlighting Proteins: The Case of the Hexokinases

Abstract: Moonlighting proteins are defined as proteins with two or more functions that are unrelated and independent to each other, so that inactivation of one of them should not affect the second one and vice versa. Intriguingly, all the glycolytic enzymes are described as moonlighting proteins in some organisms. Hexokinase (HXK) is a critical enzyme in the glycolytic pathway and displays a wide range of functions in different organisms such as fungi, parasites, mammals, and plants. This review discusses HXKs moonligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 276 publications
1
37
0
Order By: Relevance
“…Despite glycolysis being an essential and highly conserved metabolic pathway, all the glycolytic enzymes also have nonenzymatic moonlighting functions. These include the long-known structural functions of the lactate dehydrogenase B4 and α-enolase [ 61 , 62 ], the RNA-enzyme-metabolite functions of the HKs, and other glycolytic enzymes [ 63 , 64 ], yet unclear function of HKs in the cell nucleus [ 65 , 66 ], immune receptor function of HK2 [ 67 ], apoptosis inhibition by HK2 [ 68 , 69 ], and the glucose-sensing function of HKs [ 70 ]. The mechanism of the glucose-sensing function of HKs remains unclear and we speculate that the glucose-sensing function might be responsible for the observed differences between the cells with catalytically dead HK1 (“lack of glucose signal” present) and without any HK1 (“lack of glucose signal” absent).…”
Section: Discussionmentioning
confidence: 99%
“…Despite glycolysis being an essential and highly conserved metabolic pathway, all the glycolytic enzymes also have nonenzymatic moonlighting functions. These include the long-known structural functions of the lactate dehydrogenase B4 and α-enolase [ 61 , 62 ], the RNA-enzyme-metabolite functions of the HKs, and other glycolytic enzymes [ 63 , 64 ], yet unclear function of HKs in the cell nucleus [ 65 , 66 ], immune receptor function of HK2 [ 67 ], apoptosis inhibition by HK2 [ 68 , 69 ], and the glucose-sensing function of HKs [ 70 ]. The mechanism of the glucose-sensing function of HKs remains unclear and we speculate that the glucose-sensing function might be responsible for the observed differences between the cells with catalytically dead HK1 (“lack of glucose signal” present) and without any HK1 (“lack of glucose signal” absent).…”
Section: Discussionmentioning
confidence: 99%
“…A classic example is enolase, which is part of the glycolytic pathway, but which is also involved in RNA degradation ( Henderson and Martin, 2013 ). However, the number of known moonlighting proteins has increased drastically in recent years ( Jeffery, 2020 ; Liu and Jeffery, 2020 ; Singh and Bhalla, 2020 ; Beaufay et al, 2021 ; Rodríguez-Saavedra et al, 2021 ; Turek and Irving, 2021 ). An indication that the archaeal proteins might have two different functions is the recent observation that the eukaryotic eIF2Bα still has the ability to bind sugar phosphates with high affinity, e.g., fructose-6-phosphate has a K D of 9.4μM ( Hao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hexokinase associates with VDAC, inhibiting apoptosis by preventing the release of cyt c in mammalian mitochondria ( Azoulay-Zohar et al, 2004 ; Abu-Hamad et al, 2008 ; Shoshan-Barmatz et al, 2008 ). There is also evidence indicating that HK bound to VDAC inhibits the formation of MPTP in plant mitochondria ( Godbole et al, 2013 ; Rodríguez Saavedra et al, 2021 ). A functional association between HK and VDAC has been reported in beetroots, where it was observed that the ATP produced by oxidative phosphorylation in the mitochondrial matrix is preferentially channeled toward the HK bound to VDAC ( Alcántar-Aguirre et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the antiapoptotic VDAC-binding proteins found in both animals and plants is hexokinase (HK). This enzyme, associated with VDAC, not only catalyzes the phosphorylation of glucose using preferentially the ATP produced by respiring mitochondria ( Pedersen, 2008 ; Alcántar-Aguirre et al, 2013 ) but also inhibits PCD ( Godbole et al, 2013 , reviewed in Rodríguez Saavedra et al, 2021 ). In contrast, it has been proposed that VDAC associates with some mitochondrial inner membrane proteins, such as the adenine nucleotide and/or the phosphate translocators, to form MPTP ( Takahashi and Tateda, 2013 ; Hurst et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%